Analysis of Factors Affecting Teacher Professionalism (Case Study of SMA/SMK teachers in South Tangerang City) - Irvana Arofah; Besse Arnawisuda Ningsi; Awaluddin Tjalla; Iva Sarifah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Teachers are one of the most important elements of the school education system, and as pioneers in implementing the learning process, teachers attract public attention for their dedicated and loyal work ethic. This study aims to examine the factors that influence the professionalism of SMA/SMK teachers in South Tangerang City in terms of teacher competence, principal leadership and work motivation. the sample was taken at random a number of 150 teachers. The analysis used in this study uses path analysis with the help of SPSS version 25 software. The results of the research on the sub-structure equation I show that the variables of teacher competence and principal leadership have a significant and significant influence on teacher work motivation. In the sub-structure equation II shows that the competence of teachers, Principal leadership and teacher work motivation have an influence on teacher professionalism. Teacher competence has a significant effect on teacher professionalism, both directly and indirectly through teacher work motivation with values of 0.431 and 0.097 respectively. Likewise, the principal's leadership has a significant effect on teacher professionalism, both directly and indirectly through teacher work motivation with values of 0.188 and 0.047, respectively.